Information Models to Manage Complexity for an Integrated Knowledge Project (diségno, 2019)
The study aims to identify optimal workflows to create information models oriented to the management and the knowledge of architectural heritage in a state of ruin, through the analysis of the critical issues found in the parametric modeling of the existing artifact. The methodology is aimed at analysing possible criteria for the enhancement of the data detected in the transition from point cloud to a semantic model, and the management of the level of graphic detail (LoG, Level of Geometry) and information attributes (LoI, Level of Information), in order to define possible procedures to measure the Level of Reliability of the survey. The case study is the Mother Church of the ancient Misterbianco (Catania), one of the rare surviving vestiges of the eruption of Mount Etna in 1669 and the ear- thquake in Val di Noto in 1693. Thanks to its state of preservation and its cultural relevance, it represents the ideal case study for the proposed experimentation. (R.G., M.L.T., C.S.)
Keywords: laser scanning; fotogrammetria; 3D modeling; H-BIM; livelli di accuratezza e affidabilità